The energy method for elastic problems with non-homogeneous boundary conditions - Quintanilla, Ramon (Zielona Góra: Uniwersytet Zielonogórski)
In this paper we propose the weighted energy method as a way to study estimates of solutions of boundary-value problems with non-homogeneous boundary conditions in elasticity. First, we use this method to study spatial decay estimates in two-dimensional elasticity when we consider non-homogeneous boundary conditions on the boundary.
Keywords: weighted energy method; decay estimates; Navier equations; non-homogeneous boundary conditions